Exploring the Effects of Visual Frame and Matching Direction on the Vertical-Horizontal Illusion. (December 2017) - Gavilán, José M.; Rivera, Daniel; Guasch, Marc; Demestre, Josep; García-Albea, José E.
The work presented here uses an adjustment method to test the vertical-horizontal illusion across four different configurations: a cross-shape, an L-shape, an inverted-T and a rotated-T. We examine the modulatory role of the variables visual frame and direction of the adjustment on the illusory effect. Two experiments were performed, one with rectangular and one with curvilinear visual frames. Our data show that in both experiments, the size of the expected illusion increases from the cross-shape to the L-shape and from the L-shape to the inverted-T, where it reaches its maximum. In the rotated-T, the illusion reverses reaching a significant effect in the opposite direction. This pattern of results appears consistently across different experimental conditions, although the variability in the amount of illusory effect seems to be modulated by the intervention of the two variables examined. A dissection of the vertical-horizontal illusion has been carried out in terms of a two-factor explanation – anisotropy and bisection – interacting in different ways across configurations.